ANALISIS PENERIMAAN PAJAK MAKAN/MINUM DAN RETRIBUSI SEWA TEMPAT UMKM PASAR SENJA GELORA DALAM MENINGKAKAN PENDAPATAN ASLI DAERAH KABUPATEN SIKKA - Ristanti, Andriani; Jaeng, Wihelmina M. Yulia; Lamawitak, Paulus Libu (Jurnal Projemen UNIPA, 2025)
This research aimed to determine the level of food/drink tax revenue and rent retribution in 2022–2024, as well as the government’s efforts to increase the regional gross income of Sikka Regency through the Micro, Small, and Medium Enterprises Sector in Pasar Senja Gelora. This research used a descriptive method with a qualitative approach. Data were collected through observation, interview, and documentation. The research results showed that the income from food/drink tax revenue and rent retribution had increased annually, making a positive contribution to regional gross income in Sikka Regency.The regional government tried to increase the income of this sector through direct socialization to the actors regarding the Sikka Regency Regional Regulation Number 5 of 2023 concerning Regional Taxes and Regional Retributions. This socialization aimed to raise awareness, improve understanding, and obey the regulations of tax revenue and rent retribution. Thus, this sector can be a significant income source for increasing the regional gross income of Sikka Regency.